ANALISIS PERKEMBANGAN JUMLAH PENDUDUK DAN TINGKAT PENGANGGURAN TERBUKA DI KOTA PEKANBARU - Riati Bakce (Menara Ilmu, 2020)
Abstract :This study aims to (1). Analyze the development and trend of population in Pekanabru City; (2). Analyzing the development and trends of the unemployment rate in Pekanabru City and (3). Analyzing the effect of population growth on the level of open unemployment in Pekanbaru City. The data was obtained from BPS publications namely Pekanbaru City in the 2011 to 2017 period. Data analysis was descriptive analysis and quantitative analysis. Descriptive analysis by calculating population growth rates, determining trends with the least squares method. Quantitative analysis using simple linear regression analysis. The findings in this study include: The development of the population of Pekanbaru City from 2011 to 2017 increased with a declining population growth rate; Open unemployment rate in Pekanbaru City fluctuates with a trend that tends to increase and population growth has no significant effect on the level of open unemployment in Pekanbaru City. Keywords: Total Population, Open Unemployment Rate